Prioritas Pengentasan Kemiskinan Dalam Perspektif Pembangunan Daerah - Pohan, Abi Fajri; Khairani, Khairani (Nagari Law Review, 2025)
Poverty has the meaning of a condition or situation where a person cannot afford to maintain himself in social life and the inability to utilize his mental or physical energy in society. The purpose of this study is to examine and analyze efforts that can be made by regional heads in overcoming and minimizing poverty in West Sumatra. The research method used is qualitative normative juridical. The results of this study are that the priority of poverty alleviation in the perspective of regional development should prioritize the benefits of regional development carried out by prioritizing the poor in the implementation of development in each region where there are still poor people. The suggestion from this study is that the government is expected in its duties and responsibilities as the executor of the function of the government system to prioritize regional development based on systems or programs that have standard provisions for welfare values ​​in the form of regulations in following up and eliminating poverty gradually so that the provisions in Pancasila and the 1945 Constitution can be created properly.